Arterial hypoperfusion as a negative predictive marker for primary hepatic malignancies treated with Y-90 glass microsphere transarterial radioembolization - Kalaghchi, Bita; Ince, Semra; Barnes, Justin; Kiser, Kendall; Chin, Re-I; Mikell, Justin; Badiyan, Shahed; Garcia, Jose; Zoberi, Jacqueline; Doyle, Maria Bernadette Majella; Tan, Benjamin; Kim, Seung; et al. (Frontiers in Oncology, 2024)
Background Radioembolization with yttrium-90 (Y-90) is utilized to treat primary liver malignancies. The efficacy of this intra-arterial therapy in arterially hypoperfused tumors is not known. Methods We reviewed data of patients with primary liver tumors treated with Y-90 prescription doses of at least 150 Gy. Baseline patient characteristics, treatment history, imaging-based tumor response assessments, and clinical outcome metrics were recorded. Tumors were classified as arterially hyperperfused versus hypoperfused on post-TARE Y-90 SPECT/CTs or pre-TARE hepatic perfusion SPECT/CTs. Perfusion status was correlated with tumor response assessments and clinical outcomes. Cox proportional hazards models were utilized to compare survival and progression-free survival. Inverse probability weighting was utilized to account for clinical factors and adjusted multivariable proportional hazards analyses to examine the relationship of quantitative perfusion and cancer outcomes. Results Of 400 Y-90 treatments, 88 patients received a prescribed dose of at least 150 Gy and had pre- or post-treatment SPECT/CT images. 11 and 77 patients had arterially hypoperfused and hyperperfused lesions, respectively. On dedicated liver MRI or CT at 3 months after Y-90, the complete response rates were 5.6% and 16.5% in the hypoperfused and hyperperfused cohort, respectively (P = 0.60). When controlling for various clinical features, including tumor histology, patients with arterially hypoperfused tumors had significantly shorter progression-free survival (HR 1.87, 95% CI - 1.03 - 3.37, P = 0.039) and greater elsewhere liver (HR 3.36, 95% CI = 1.23 - 9.20, P = 0.019) and distant failure (HR 7.64 (2.71 - 21.54, P < 0.001). In inverse probability weighted analysis, patients with arterially hypoperfused tumors had worse overall survival (P = 0.032). In the quantitative analysis, lower levels of lesion perfusion were also associated with worse clinical outcomes, again controlling for tumor histology. Conclusion Compared to arterially hyperperfused tumors, hypoperfused primary liver tumors treated with Y-90 may have worse clinical outcomes.